Exploring CAZymes Differences in Pediococcus acidilactici Strain OM681363 and Lacticaseibacillus paracasei Strain ON606241 Based on Whole-Genome Sequencing - Miao Lin; Shakib Mohamed Jama; Zhiqiang Cheng; Yujie Zong; Yanjing Su; Wengboyang Liu; Li Liu (Fermentation)
Lactic acid bacteria (LAB) is a collective term for bacteria capable of producing lactic acid from fermentable carbohydrates. Despite their widespread presence in the gastrointestinal tracts of humans and animals, where they play important physiological roles, functional analysis of specific strains from particular sources requires further enrichment. The objective of this study was to explore the differences between Pediococcus acidilactici OM681363 and Lacticaseibacillus paracasei ON606241, both isolated from the rumen of Chinese Holstein dairy cows, using whole-genome sequencing. The results indicate that P. acidilactici OM681363 contained three CRISPR fragments and numerous enzymes involved in carbohydrate degradation. Additionally, P. acidilactici OM681363 possessed more genes related to fiber degradation, especially cellobiose, and the sole carbon source experiment also confirmed this. However, it lacked genes associated with polysaccharide lyase. In contrast, L. paracasei ON606241 was found to be more specialized in breaking down non-fiber carbohydrates, producing more acetic and lactic acids. Overall, P. acidilactici OM681363 may have a greater capacity to degrade complex carbohydrates, while L. paracasei ON606241 appears to specifically target non-fiber carbohydrates.